Приведите одночлен к стандартному виду: -2 * а^2 * -3b^3 = 3a * -2b^2 * 3b =ab^2^2*-4a^2=b*-3a^3*a^2=ab*-2*4a^3=ab*4a*-3b^3=2ab^2*-3*b=

Приведите одночлен к стандартному виду:
 (-2) * а^2 * (-3)(b)^3 = 
3a * (-2b)^2 * 3b =
(ab^2)^2*(-4a)^2=
b*(-3a)^3*a^2=
ab*(-2)*(4a)^3=
ab*4a*(-3b)^3=
(2ab)^2*(-3)*b=

  • (-2) * а^2 * (-3)(b)^3 =  6а^2b^3

    3a * (-2b)^2 * 3b= 36ab^3

    (ab^2)^2*(-4a)^2=16a^4b^4

    b*(-3a)^3*a^2= -27a^5b

    ab*(-2)*(4a)^3= -128a^4b

    ab*4a*(-3b)^3= -108a^2b^4

    (2ab)^2*(-3)*b=-12a^2b^3